2010
DOI: 10.1002/jmri.22068
|View full text |Cite
|
Sign up to set email alerts
|

Validation of functional diffusion maps (fDMs) as a biomarker for human glioma cellularity

Abstract: Purpose: To present comprehensive examinations of the assumptions made in functional diffusion map (fDM) analyses and provide a biological basis for fDM classification. Materials and Methods:Sixty-nine patients with gliomas were enrolled in this study. To determine the sensitivity of apparent diffusion coefficients (ADCs) to cellularity, cell density from stereotactic biopsy specimens was correlated with preoperative ADC maps. For definition of ADC thresholds used for fDMs, the 95% confidence intervals (CI) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
208
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 245 publications
(219 citation statements)
references
References 21 publications
6
208
0
5
Order By: Relevance
“…7 Conversely, others have suggested that these persistent restricted-diffusion lesions may correspond to areas of atypical necrosis in the setting of anti-VEGF treatment-induced chronic hypoxia. 9 In the current study, we have built on previous studies by characterizing the time-dependent changes in these lesions and determining whether these patients differ with respect to patient outcomes compared with carefully matched controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Conversely, others have suggested that these persistent restricted-diffusion lesions may correspond to areas of atypical necrosis in the setting of anti-VEGF treatment-induced chronic hypoxia. 9 In the current study, we have built on previous studies by characterizing the time-dependent changes in these lesions and determining whether these patients differ with respect to patient outcomes compared with carefully matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…4 Alternative MR imaging techniques such as DWI have shown promise in defining both tumor response and nonenhancing tumor progression in the setting of bevacizumab treatment. 5,6 ADC, a measure reflecting the magnitude of free water mobility obtained by using DWI, can be reduced by the presence of increased cell membranes that typify hypercellular tumor 7,8 ; however, ADC can be reduced by other biophysical parameters, including increased viscosity; protein content, such as occurs in abscess 9 ; and movement of water from the extraceullar to intracellular space as seen in ischemia or cytotoxic edema. 10 Recently, investigators and clinicians have noted an interesting phenomenon in patients with malignant glioma treated with bevacizumab, consisting of lesions with conspicuously low ADC, which persists over long periods of time.…”
mentioning
confidence: 99%
“…The apparent diffusion coefficient (ADC) measured using DWI has been shown to be inversely associated with cell density [29,30], as water diffusivity is restricted with increased cell density and barriers to free water mobility. Consistent with this observation, several studies have demonstrated progressive tumor exhibiting lower ADC (~1.0-1.3 µm 2 /ms) compared with pseudoprogression (>1.3 µm 2 /ms) [31][32][33].…”
Section: Diffusion Mrimentioning
confidence: 99%
“…One common measurement obtained from DWI is the apparent diffusion coefficient (ADC). ADC is an estimate of the magnitude of the diffusion of water molecules within the tissue, and there is a strong negative correlation between the ADC and tumor cellularity in gliomas [16,17]. Perfusion-weighted imaging (PWI) is an MRI modality that gives insights into the delivery of blood to tissues by monitoring a bolus of contrast agent as it passes through the blood vasculature.…”
Section: Introductionmentioning
confidence: 99%